Secrets of power negotiating : inside secrets from a master negotiator - Dawson, Roger, 1940- (Career Press, 2001)
Roger Dawson explains every aspect of the negotiating process in this updated edition of Secrets of Power Negotiating. His technique allows the negotiator to win and leave the other party feeling that they have won too.